2024
DOI: 10.3389/fmed.2024.1294290
|View full text |Cite
|
Sign up to set email alerts
|

Changes in selected hematological parameters in patients with type 1 and type 2 diabetes: a systematic review and meta-analysis

Getachew Mesfin Bambo,
Daniel Asmelash,
Ermiyas Alemayehu
et al.

Abstract: BackgroundDiabetes mellitus is a chronic metabolic disorder that causes hyperglycemia and various life-threatening health problems. Although hematological parameters play a significant role in the progression and pathogenesis of diabetes, many studies have explored contradictory findings. Therefore, this evidence-based study aimed to determine the pooled mean difference of white blood cell and red blood cell parameters in diabetic patients in order to investigate hematological dysfunctions in type 1 and type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Significant increases in the number of neutrophil, monocyte–macrophage, and platelet cells have been recorded in type 2 DM patients during the inflammation process. In a systematic meta-analysis study examining the changes in hematologic parameters of patients with type 2 DM and type 1 DM and a control group of healthy individuals, it was shown that patients with type 2 DM had significantly higher absolute neutrophil, absolute monocyte, absolute lymphocyte, and absolute basophil counts and relative neutrophil and basophil counts [ 23 ]. In addition, another study reported that hematologic parameters, such as the neutrophil-to-lymphocyte ratio (NLR) and monocyte-to-platelet ratio, were higher in patients with diabetes and that these increases could be considered a sign of inflammatory response [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Significant increases in the number of neutrophil, monocyte–macrophage, and platelet cells have been recorded in type 2 DM patients during the inflammation process. In a systematic meta-analysis study examining the changes in hematologic parameters of patients with type 2 DM and type 1 DM and a control group of healthy individuals, it was shown that patients with type 2 DM had significantly higher absolute neutrophil, absolute monocyte, absolute lymphocyte, and absolute basophil counts and relative neutrophil and basophil counts [ 23 ]. In addition, another study reported that hematologic parameters, such as the neutrophil-to-lymphocyte ratio (NLR) and monocyte-to-platelet ratio, were higher in patients with diabetes and that these increases could be considered a sign of inflammatory response [ 24 ].…”
Section: Discussionmentioning
confidence: 99%